Effects of chronic swimming exercise and cannabidiol on metabolic and inflammatory gene expression in obese rats - Hepsert, Sezgin; Dalkılıç, Lütfiye Kadioglu; Özdemir, Emrah; Aydınlı, İbrahim; Ugurlu, Fatih Mehmet; Dalkılıç, Semih; Kılıç, Yakup (Bmc, 2026)
Background In this study, we aimed to investigate the effects of exercise and cannabidiol on the expression of target genes involved in metabolic regulation and inflammation-related molecular pathways in rats made obese by a high-fat diet. Method The study with a randomized controlled experimental design was conducted on 40 male Sprague-Dawley rats aged 8 weeks. The rats were randomly assigned to 5 groups with 8 rats in each group (Control, Obese Control, Obese Exercise, Obese CBD, Obese Exercise CBD).The intervention protocol consisted of 6 weeks of swimming exercise (30 min/day, 5 days/week) and CBD (10 mg/kg/day/week) by oral gavage.The expression levels of the target genes examined in adipose tissue and liver tissues were determined by quantitative real-time PCR. SPSS 22.0 (IBM, Armonk, NY, USA) package program was used for data analysis. The data were analyzed using One Way Anova for the determination of significant differences and LSD test for the determination of significant differences between groups. Results Upon examination of the findings, significant differences were observed between the groups in terms of BMI (p=0.001) and blood sugar levels (p=0.001) after 6 weeks of exercise and cannabidiol application. Significant differences were observed in the LKB1 (p=0.045) and PERK (p=0.013) parameters examined in liver tissue, while no significant differences were observed in the SREB1 (p=0.209) target gene. Significant differences were observed in the LKB1 (p=0.009) and PERK (p=0.011) parameters examined in adipose tissue, while no significant difference was detected in the SREB1 (p=0.060) target gene. Conclusion In conclusion, it was determined that the 6-week chronic swimming exercise and cannabidiol application, particularly the combined intervention, resulted in improvement in the intervention groups compared to the OC group in the target genes examined.The absence of significant differences between the C group and the intervention groups indicates that complete improvement was not achieved. Based on these data, it is thought that the combined application of regular exercise and controlled doses of cannabidiol may be beneficial in improving metabolic health parameters in obese individuals.These results highlight the potential of integrating exercise with natural bioactive compounds in obesity prevention strategies.
Keywords: Exercise; Obesity; Glucose Metabolism; Oxidative Stress; Chronic Inflammation